Emerging therapies for the treatment of rare pediatric bone disorders - Thrailkill, Kathryn M.; Kalaitzoglou, Evangelia; Fowlkes, John L. (Frontiers in Pediatrics, 2022)
In recent years, new therapies for the treatment of rare pediatric bone disorders have emerged, guided by an increasing understanding of the genetic and molecular etiology of these diseases. Herein, we review three such disorders, impacted by debilitating deficits in bone mineralization or cartilage ossification, as well as the novel disease-modifying drugs that are now available to treat these conditions. Specifically, we discuss asfotase alfa, burosumab-twza, and vosoritide, for the treatment of hypophosphatasia, X-linked hypophosphatemia and achondroplasia, respectively. For each skeletal disorder, an overview of the clinical phenotype and natural history of disease is provided, along with a discussion of the clinical pharmacology, mechanism of action and FDA indication for the relevant medication. In each case, a brief review of clinical trial data supporting drug development for each medication is provided. Additionally, guidance as to drug dosing and long-term monitoring of adverse events and pediatric efficacy is presented, to aid the clinician seeking to utilize these novel therapies in their practice, or to become familiar with the healthcare expectations for children receiving these medications through specialized multidisciplinary clinics. The availability of these targeted therapies now significantly augments treatment options for conditions in which past therapy has relied upon less specific, symptomatic medical and orthopedic care.